Sistem Informasi Pendugaan Kekerasan Terhadap Perempuan dan Anak Menggunakan Metode Small Area Estimation - Misbahul Munir S; Nurul Mutiah; Syahru Rahmayudha; Renny Puspita Sari (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2022)
Based on data obtained from the SIMFONI-PPA Application, the Office of Women's Empowerment, Child Protection, Population Control and Family Planning (DP3AP2KB) Sambas Regency, in 2017 there were 95 cases of violence against women and children in Sambas Regency, then in 2018 there were 43 cases, followed by in 2019 as many as 49 cases, and in 2020 as many as 64 cases. This shows an increasing trend in the number of cases of violence that occur from year to year. The increasing trend is caused by the lack of access to information to make complaints, the processing of data on areas of violence that has not been integrated, so that the government does not have up-to-date data to anticipate. To support DP3AP2KB in handling and preventing violence, this research builds a system based on the estimation of violence against women and children by utilizing the Small Area Estimation Method, especially the IDW interpolation technique. This research was carried out by processing data through the ArcGIS application to determine the pattern of areas prone to violence, using interpolation techniques to predict unmeasured variables at various locations, with IDW assuming that the closer a point is to an unknown point, the greater the effect. . IDW uses the values measured at points around the location, to estimate the value of the variable at the location in question. Then the results of data processing is implemented in a web-based geographic information system. The system that has been built has been tested using the black box method and calculated using a Likert scale, obtaining a value of 86.20% which is included in the Very Good category.